Optimisation of a 180° U-shaped bend shape for a turbine blade cooling passage leading to a pressure loss coefficient of approximately 0.6. (June 2016) - Namgoong, Howoong; Ireland, Peter; Son, Changmin
The U-bend which turns flow through 180° is encountered in many applications in mechanical and aerospace engineering systems. One important example occurs in modern turbine blade cooling systems, where the internal cooling passages is threaded radially outwards and inwards to form a multi-pass arrangement where straight passages are connected with U-bends. The main purpose of the present investigation was to focus on finding a 3D U-bend configuration with minimum pressure loss using the 3D CAD-based surface parameterisation method. The design of experiment technique and surrogate design space model were successfully applied by the authors, as opposed to direct numerical optimisation, to reduce the computational cost. A standard Reynolds-averaged Navier–Stokes (RANS) computational fluid dynamics method with the Spalart–Allmaras one equation turbulence model was selected for. Even though the simple RANS with the one equation turbulence model cannot simulate the highly complex U-bend flow physics precisely, the optimisation process was able to identify an optimum U-bend configuration which achieved a 63.3% pressure loss reduction, relative to the datum configuration, yielding the lowest loss U-bend in the literature. The authors also performed careful experiments to confirm their predictions and the performance of the optimum U-bend configuration identified by this work was validated.